Porcentagem de eclosão de ovos de haematobia irritans (l.) (diptera: muscidae) em laboratório - Ferraz Lima, Luiz Gustavo [UNESP] (2010)
The laboratory production of the horn fly is still an important resource for research. Several authors have already observed that viability of immature stages varies according to arthropod species. In this study were observed the Haematobia irritans egg percentage hatching. Bovine faeces was obtained from animals grazing pastures (Brachiaria decumbens) was collected and used immediately or placed in a refrigerator (2-3 degrees C). Horn flies were captured in bovine to get eggs placed in filter paper on dung and incubate at 32 +/- 2 degrees C and 80% RH for larvae raring. The results were based on the number of hatched eggs and we observed 83,0% percent of larvae rearing.